Changes of hippocampus proteomic profiles after blueberry extracts supplementation in APP/PS1 transgenic mice. (2nd January 2020) - Li, Hai-qiang; Tan, Long; Yang, Hong-peng; Pang, Wei; Xu, Tong; Jiang, Yu-gang
Abstract : Objective: To examine protein changes in the hippocampus of APP/PS1 transgenic mice after blueberry extracts (BB) intervention. Methods: Eight APP/PS1 transgenic mice were randomly assigned to Alzheimer's disease (AD)+BB group ( n =4) and AD+control group ( n =4). After a 16-week treatment, 2-DE and MALDI-TOF-MS were used to compare the proteomic profiles of the hippocampus in the two groups and Western blot was used to confirm the important differentially expressed proteins. Results: Twelve proteins were differentially expressed between the two groups. Nine of them were identified. Cytochrome b-c1 complex subunit 6, beta-actin, dynamin 1, and heat shock cognate 71 were up-regulated in AD+BB group, while a-enolase, stress-induced-phosphoprotein 1, malate dehydrogenase (MDH), MDH 1, and T-complex protein 1 subunit beta were down-regulated, respectively. Importantly, some of the identified proteins (e.g. dynamin 1) are known to be involved in cognitive impairment. Western blot analysis of hippocampus dynamin 1 expression confirmed the proteomic findings. Conclusions: The consumption of BB modulates the expression of proteins that are linked to the improvements of cognitive dysfunction in hippocampus of APP/PS1 transgenic mice.